5 - Colonial Encounters: A Danish Planter in German East Africa - Marianne Rostgaard, (Afrika Zamani, 2022)
In 1888, Christian Lautherborn set out to establish a cotton plantation for the German East Africa Company in Pangani, Tanzania. Little did he know that he was heading out at a dramatic moment, and would soon (literally) be caught in the crossfire of a war between the coastal Africans, the Zanzibar government and German imperialist interventions. While in Tanzania, Lautherborn wrote a series of letters, some published in a local Danish newspaper and some written privately to familyA substantial number of Christian Lautherborn’s letters home were printed in a newspaper, Vendsyssel Tidende, as ‘Letters from our correspondent in German East Africa’. This article will take its point of departure in the analysis of differences between what may be termed the ‘public’ and the ‘private’ discourses in the letters. Parts of the letters may be read as a contribution to the formation of a colonial discourse in Denmark/Europe. Here one finds a number of familiar stereotypes about Africa and Africans. On the other hand, some of the letters, often eyewitness accounts of incidents that diverge from the common colonial discourse, suggest very different interpretations. The letters may thus be read both as a way of negotiating African experiences and European expectations and also as evidence of cultural adaptation and hybridity. The paper will therefore comment on discrepancies between common stereotypes present in the letters about the African’s childishness, laziness etc. and Christian Lautherborn’s actions as a plantation manager and member of colonial society. A careful reading of Lautherborn’s letters a so reveals a number of contradictions between what he says and what he does.